BINTU SYATI’ DAN PENAFSIRANNYA TERHADAP SURAH AL-‘ASR DALAM KITAB AT-TAFSIR AL-BAYANI LIL QUR’ANIL KARIM - Wali Ramadhani (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2018)
This article discusses about the biography of Bintu Syati’ and her bayani interpretation. Her Interpretation work titled at-Tafsir al-Bayani lil Quranil Karim is the best representation of the methodology of the Quran interpretation with a literary nuance initiated by her own husband, Amin al-Khuli. The author, in this article, also describes the application of Bayani interpretation method in QS al-‘Asr.